HPLC with electrochemical and fluorescence detection procedures for the diagnosis of inborn errors of biogenic amines and pterins - Ormazabal, Aida; García-Cazorla, Angels; Fernández, Yolanda; Fernández-Álvarez, Emilio; Campistol, Jaume; Artuch, Rafael (Journal of neuroscience methods, 2005)
The analysis of biogenic amines (BA) and pterins in cerebrospinal fluid (CSF) is essential for the early diagnosis of neurotransmission defects in the paediatric age. Our aim was to standardize previously reported HPLC procedures for the analysis of BA and pterins in CSF and to establish reference values for a paediatric population. Samples from 127 subjects (age range 11 days to 16 years; average 3.8) were analyzed by HPLC with electrochemical and fluorescence detection. Both BA (homovanilic and 5-hydroxyindoleacetic acid) and pterins (neopterin and biopterin) concentrations in CSF showed a negative correlation with age. This finding led us to stratify reference values into six groups according to age. In conclusion, analysis of BA and pterins in CSF by HPLC procedures is a useful set of tools for the diagnosis of inborn errors of metabolism of these compounds. The establishment of reference intervals may be difficult, since there is a strong correlation between BA concentrations and the age of controls and, as a result, a large number of CSF samples from control populations would be necessary for this purpose.